2002
DOI: 10.1179/136217102225006886
|View full text |Cite
|
Sign up to set email alerts
|

Processes and properties of deposits in electrospark deposition

Abstract: In the electrospark deposition of a material, a high current is conducted through an oscillating electrode and a substrate for a very short period of time. When the electrode is moved away from the surface, an arc is formed momentarily, causing melting of the electrode surface for a short time. In the present work, the process was monitored in real time using a high speed camera, permitting determination of the mode of mass transfer from the electrode to the substrate, the number and size of droplets, and arc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 3 publications
3
37
0
1
Order By: Relevance
“…The material transferred from Mg-Nd electrode by setting 3 was largest among the three settings. Calculations showed that in the present study the pulse energy could vary between a few tenths of a joule and a little more than 4 J [9]. This means that by different parameter settings, the pulse energy is quite different, which causes different material transfer from the electrode.…”
Section: Surface and Cross-section Morphologies Of The Coatingsmentioning
confidence: 81%
See 1 more Smart Citation
“…The material transferred from Mg-Nd electrode by setting 3 was largest among the three settings. Calculations showed that in the present study the pulse energy could vary between a few tenths of a joule and a little more than 4 J [9]. This means that by different parameter settings, the pulse energy is quite different, which causes different material transfer from the electrode.…”
Section: Surface and Cross-section Morphologies Of The Coatingsmentioning
confidence: 81%
“…The two primary components of this machine are the power supply and the torch/applicator head. The power supply is to supply the instantaneous discharging energy for coating deposition [7][8][9]; the torch/applicator head, primarily for coating applications. The maximum output power of the HEMAA machine is 1.5 kW (only can be output by 1500 W, 14% × 1500 W, 28% × 1500 W, 42% × 1500 W), with output of voltage 40 V, 60 V, 80 V and 100 V, continuously regulating frequency.…”
Section: High-energy Micro-arc Alloying Machinementioning
confidence: 99%
“…e relationship between process parameters and the deposit structure has been also investigated [33][34][35][36]. Only few studies are related to the utilisation of ESD as a repair technology.…”
Section: Introductionmentioning
confidence: 99%
“…Many works have studied the mass transfer that occurs during the ESD process [25][26][27], which is paramount to produce a high wear-resistant coating [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Since this process allows the use of any electrical conductor material as the electrode, it can be possible to form ultra hard ceramic or cermet coatings on the metallic substrates. This process can produce metallurgical bonding between the coatings and substrates depending on the process parameters, resulting in a much better coating adhesion, compared to other low-energy coating processes [5,6]. Thus, the pair of the electrode and the substrate material, which were selected, is an important parameter for coating process [7].…”
Section: Introductionmentioning
confidence: 99%